A kind of multi-level mesoporous carbon and preparation method thereof

The preparation of multi-stage mesoporous carbon by direct spray cracking method solves the problems of low efficiency and high cost of carbon materials in the prior art, and achieves rapid, uniform and high graphitization of carbon materials.

CN119430150BActive Publication Date: 2025-04-04QINGHYDROGEN (BEIJING) TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510046298.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing carbon material preparation process is low efficiency and high cost, making it difficult to achieve rapid carbonization and precise control of the microstructure of carbon materials.

Method used

The first soluble carbon source, pore-forming agent, and alcohol solvent are mixed with water by using direct spray cracking method, and the first solidification treatment is performed to form a first precursor, and then a cladding layer is formed on its surface to obtain a second precursor, and mixed with a salt solution for ultrasonic spray-cracking carbonization treatment to prepare multi-stage mesoporous carbon.

Benefits of technology

The rapid preparation of multi-stage mesoporous carbon is achieved, with good particle molding, uniform particle size, and dispersion, high degree of graphitization, large interlayer pores, micropores and mesoporous multi-stage pores, reducing production costs and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430150B_ABST
    Figure CN119430150B_ABST
Patent Text Reader

Abstract

The present invention provides a multi-level mesoporous carbon and a preparation method thereof, belonging to the technical field of carbon materials. The present invention mixes a first soluble carbon source, a pore-forming agent, an alcohol solvent and water, and performs ultrasonic spray-freezing treatment on the obtained first soluble carbon source solution, and then performs a first solid treatment to obtain a first precursor; an aqueous solution of a second soluble carbon source is coated on the surface of the first precursor, and a coating layer is formed on the surface of the first precursor by freezing to obtain a second precursor; the second precursor is mixed with a salt solution, and the obtained second precursor liquid is subjected to ultrasonic spray-cracking carbonization treatment to obtain the multi-level mesoporous carbon. The present invention adopts a direct spray cracking method to prepare multi-level mesoporous carbon with excellent comprehensive performance, high production efficiency and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon materials, and in particular to multi-level mesoporous carbon and a preparation method thereof. Background Art

[0002] Carbon materials play a key role in the fields of catalysis, electrochemical energy storage and environmental governance. In particular, the optimization of the preparation process is crucial in improving the uniformity of carbon material performance, pore structure regulation and conductivity. Currently, traditional processes for preparing high-quality carbon materials, such as sol-gel, pyrolysis and chemical vapor deposition (CVD), usually involve complex multi-step operations. When achieving rapid carbonization and precise control of the microstructure of carbon materials, existing processes often face problems of low efficiency and high cost. Summary of the invention

[0003] The purpose of the present invention is to provide a multi-level mesoporous carbon and a preparation method thereof. The present invention adopts a direct spray pyrolysis method to prepare multi-level mesoporous carbon with excellent comprehensive performance, high production efficiency and low cost.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing multi-level mesoporous carbon, comprising the following steps:

[0006] A first soluble carbon source, a pore-forming agent, an alcohol solvent and water are mixed, and the obtained first soluble carbon source solution is subjected to ultrasonic spray-freezing treatment, and then subjected to a first solidification treatment to obtain a first precursor;

[0007] Coating an aqueous solution of a second soluble carbon source on the surface of the first precursor, and freezing the aqueous solution on the surface of the first precursor to form a coating layer, thereby obtaining a second precursor;

[0008] The second precursor is mixed with a salt solution, and the obtained second precursor liquid is subjected to an ultrasonic spray-cracking carbonization treatment to obtain the multi-level mesoporous carbon.

[0009] Preferably, the first soluble carbon source and the second soluble carbon source independently include one or more of glucose, sucrose and fructose, the alcohol solvent includes one or more of ethylene glycol, ethanol, propanol and isopropanol; the pore-forming agent includes a non-ionic pore-forming agent; and the mass ratio of the first soluble carbon source, the pore-forming agent, the alcohol solvent and water in the first soluble carbon source solution is 1~10:0.02~0.2:1~5:5~8.

[0010] Preferably, the conditions of the ultrasonic spray-freezing treatment include: ultrasonic power of 100-500 W, flow rate of the first soluble carbon source solution of 1-5 mL / min, and freezing temperature <-60°C.

[0011] Preferably, the temperature of the first solidification treatment is -120 to -20°C, and the time is 2 to 6 hours.

[0012] Preferably, the aqueous solution of the second soluble carbon source has a concentration of 50-80 wt % and a temperature of -5-5°C.

[0013] Preferably, the particle size of the first precursor is 100-500 nm, and the thickness of the coating layer is 80-200 nm.

[0014] Preferably, the salt in the salt solution includes one or more of potassium chloride, calcium chloride and sodium chloride; the concentration of the salt solution is 20-35wt%, and the temperature of the salt solution is -55--30°C.

[0015] Preferably, the conditions of the ultrasonic spray-cracking carbonization treatment include: ultrasonic power of 100-500 W, flow rate of the second precursor liquid of 0.5-3 mL / min, and cracking carbonization temperature of 800-900 °C.

[0016] Preferably, the ultrasonic spray-cracking carbonization treatment further includes a second solidification treatment; the temperature of the second solidification treatment is 700-1400° C., and the insulation time is 2-6 hours.

[0017] The present invention provides a multi-level mesoporous carbon prepared by the preparation method of the above technical solution, with a particle size of 100-500nm, a pore size of ≤35nm, and a D / I G It is 0.5~1.5.

[0018] Beneficial effects: The present invention mixes a first soluble carbon source, a pore-forming agent, an alcohol solvent and water, and then subjects the obtained first soluble carbon source solution to ultrasonic spray-freezing treatment, and then subjects it to a first solid treatment to obtain a first precursor; an aqueous solution of a second soluble carbon source is coated on the surface of the first precursor, and a coating layer is formed on the surface of the first precursor by freezing to obtain a second precursor; the second precursor is mixed with a salt solution, and the obtained second precursor liquid is subjected to ultrasonic spray-cracking carbonization treatment to obtain the multi-level mesoporous carbon. The present invention adopts an ice template method and a pore-forming agent to prepare a first precursor, and then forms a coating layer on its surface to obtain a second precursor, and then adopts a direct spray cracking method to prepare multi-level mesoporous carbon, and the carbonization speed is fast. At the same time, the obtained multi-level mesoporous carbon has good particle forming degree and uniform particles, good particle dispersibility, high degree of graphitization, large interlayer pores, and micropores and mesoporous multi-level pores. The entire preparation process of the method provided by the present invention does not require too many complicated reagents and operations, which greatly simplifies the production process and reduces costs; and the water and alcohol solvents used in the ice template method are clean, pollution-free and reusable, which brings great convenience to production.

[0019] Furthermore, the ultrasonic spray-cracking carbonization treatment of the present invention also includes a second solidification treatment. The second solidification treatment is beneficial to ensure that the multi-level mesoporous carbon is completely carbonized, increase the uniformity and firmness of the multi-level mesoporous carbon, and at the same time help to improve the degree of graphitization. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a structural diagram of a spray cracking device in an embodiment of the present invention;

[0021] Figure 2 This is a SEM image of the hierarchical mesoporous carbon prepared in Example 1;

[0022] Figure 3 This is a SEM image of the hierarchical mesoporous carbon prepared in Example 2;

[0023] Figure 4 This is a SEM image of the hierarchical mesoporous carbon prepared in Comparative Example 1;

[0024] Figure 5 This is a SEM image of the hierarchical mesoporous carbon prepared in Comparative Example 2;

[0025] Figure 6 A comparison diagram of the pore distribution of the multi-level mesoporous carbon prepared in Example 1 and Comparative Example 2;

[0026] Figure 7 The particle size distribution diagram of the multi-level mesoporous carbon prepared in Example 1;

[0027] Figure 8 The particle size distribution diagram of the multi-level mesoporous carbon prepared in Example 2;

[0028] Fig. 9 is a Raman spectrum of carbon black particles obtained after ultrasonic spray-cracking carbonization treatment in Example 1;

[0029] Fig.10 This is a comparison diagram of the Raman spectra of the multi-level mesoporous carbon prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing multi-level mesoporous carbon, comprising the following steps:

[0031] A first soluble carbon source, a pore-forming agent, an alcohol solvent and water are mixed, and the obtained first soluble carbon source solution is subjected to ultrasonic spray-freezing treatment, and then subjected to a first solidification treatment to obtain a first precursor;

[0032] Coating an aqueous solution of a second soluble carbon source on the surface of the first precursor, and freezing the aqueous solution on the surface of the first precursor to form a coating layer, thereby obtaining a second precursor;

[0033] The second precursor is mixed with a salt solution, and the obtained second precursor liquid is subjected to an ultrasonic spray-cracking carbonization treatment to obtain the multi-level mesoporous carbon.

[0034] The present invention adopts an ice template method and a pore-forming agent, and utilizes the different freezing points of different reagents to obtain a first precursor through ultrasonic spray-freezing treatment and a first solidification treatment, and then forms a coating layer on its surface to obtain a second precursor, and then performs ultrasonic spray-cracking carbonization treatment based on a direct spray cracking method (i.e., using an ultrasonic spray device to directly spray into a tubular furnace to achieve cracking and carbonization) to obtain the multi-level mesoporous carbon, which can achieve rapid carbonization and structural control of carbon materials. Compared with traditional carbonization methods, the method of the present invention greatly shortens the processing time and is suitable for large-scale preparation of carbon materials. Specifically, the present invention, on the one hand, forms pores in a cold trap by an ice template method, which can effectively regulate the multi-level pore structure of the carbon material and enhance its specific surface area and adsorption capacity; on the other hand, the pore-forming agent forms micropores and mesopores during the carbonization process, which is conducive to further improving the electrochemical performance and mass transfer capacity of the carbon material. Therefore, the multi-level mesoporous carbon prepared by the method of the present invention has wide application potential in the fields of electrocatalyst carriers, supercapacitors, electrode materials, etc. The method of the present invention is described in detail below.

[0035] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.

[0036] The present invention mixes a first soluble carbon source, a pore-forming agent, an alcohol solvent and water, and then performs ultrasonic spray-freezing treatment on the obtained first soluble carbon source solution, and then performs a first solid treatment to obtain a first precursor. Compared with the traditional template method, the generation and removal of the ice template is only related to temperature. The present invention introduces the ice template method, and uses the difference in freezing points of different reagents to form a first precursor through ultrasonic spray-freezing treatment; the ice template (water and alcohol solvent) and the pore-forming agent form a hierarchical support skeleton of the carbon source, which gradually evaporates as the temperature rises during the ultrasonic spray-cracking carbonization treatment process, which can ensure that the microstructure and mesostructure in the carbon precursor skeleton are still well preserved when the three escape without collapse.

[0037] As an embodiment of the present invention, the first soluble carbon source may include one or more of glucose, sucrose and fructose, specifically glucose; the pore-forming agent may include a nonionic pore-forming agent, and the nonionic pore-forming agent may include one or more of hexadecyltrimethylammonium bromide (CTAB), polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, specifically CTAB; the alcohol solvent may include one or more of ethylene glycol, ethanol, propanol and isopropanol, specifically ethylene glycol; the water may be ultrapure water. As an embodiment of the present invention, the mass ratio of the first soluble carbon source, the pore-forming agent, the alcohol solvent and the water may be 1-10:0.02-0.2:1-5:5-8, further may be 5-8:0.1-0.12:3-4:5-8, specifically may be 5:0.12:3:5 or 8:0.1:4:8. The alcohol solvent and water in the present invention act as ice templates during ultrasonic spray-freezing treatment, and evaporate during the subsequent ultrasonic spray-cracking carbonization treatment, which is beneficial to increasing the interlayer pores (i.e., the gaps between particles) of the finally obtained multi-level mesoporous carbon. In the embodiment of the present invention, CTAB is used as a pore-forming agent, which can form an ordered micelle structure in the first soluble carbon source solution. In the subsequent ultrasonic spray-cracking carbonization treatment, it will leave holes after thermal decomposition to form a microporous structure and a mesoporous structure, which is beneficial to make the finally obtained multi-level mesoporous carbon not only have a higher specific surface area, but also show excellent performance in mass transfer and electrochemical reactions.

[0038] As an embodiment of the present invention, the conditions of the ultrasonic spray-freezing treatment may include: the ultrasonic power may be 100-500W, further 150-250W, and specifically 200W; the flow rate of the first soluble carbon source solution may be 1-5mL / min, specifically 1mL / min, 2mL / min, 3mL / min, 4mL / min or 5mL / min; the freezing temperature <-60°C, further -150--50°C, further -90--70°C, and specifically -80°C. In an embodiment of the present invention, the first soluble carbon source solution is specifically injected into an ultrasonic spray device, the nozzle of the ultrasonic spray device is located directly above the cold trap (the distance between the nozzle and the cold trap may be 10cm), the cold trap is aimed at and the flow rate of the first soluble carbon source solution is adjusted to 1-5mL / min for ultrasonic spraying, and the first precursor is collected in a glass container in the cold trap. In the embodiment of the present invention, by performing ultrasonic spray-freezing treatment under the above conditions, microparticles can be formed in the cold trap.

[0039] As an embodiment of the present invention, during the ultrasonic spray-freezing treatment, the ultrasonic spray is performed intermittently, specifically, it can be started for 5 seconds, then stopped for 5 seconds, and repeated as a cycle. In the embodiment of the present invention, the ultrasonic spray-freezing treatment in the above manner is used to improve the interlayer porosity of the finally obtained multi-level mesoporous carbon.

[0040] As an embodiment of the present invention, the ultrasonic spray-freezing treatment may further include sieving, and then the first solidification treatment is performed; a well-dispersed aggregate (particle size can be 80-500 mesh, specifically 200 mesh; the aggregate with a larger particle size is redissolved and subjected to the above-mentioned ultrasonic spray-freezing treatment) can be obtained by sieving, and then the first solidification treatment can be performed to obtain a first precursor with good particle size uniformity (particle size can be 100-500nm). As an embodiment of the present invention, the temperature of the first solidification treatment can be -120--20°C, further -90--70°C, specifically -80°C; the time can be 2-6h, further 3-5h, specifically 4h. In the embodiment of the present invention, the first solidification treatment is specifically performed in a freeze dryer. In the embodiment of the present invention, the first solidification treatment is performed under the above conditions, and the liquid sprayed can be quickly frozen in the cold trap, which is conducive to the rapid formation of the granular first precursor.

[0041] After obtaining the first precursor, the present invention coats the surface of the first precursor with an aqueous solution of a second soluble carbon source, and forms a coating layer on the surface of the first precursor by freezing to obtain a second precursor. As an embodiment of the present invention, the second soluble carbon source may include one or more of glucose, sucrose and fructose, and may specifically be glucose. As an embodiment of the present invention, the concentration of the aqueous solution of the second soluble carbon source may be 50-80wt%, further may be 75-80wt%, and may specifically be a saturated solution; the temperature may be -5-5°C, further may be -2-2°C, and may specifically be 0°C. As an embodiment of the present invention, the dosage ratio of the aqueous solution of the second soluble carbon source to the first soluble carbon source may be 10mL:1-10g, and may specifically be 10mL:1g, 10mL:2g, 10mL:3g, 10mL:4g, 10mL:5g, 10mL:6g, 10mL:7g, 10mL:8g, 10mL:9g or 10mL:10g. In an embodiment of the present invention, the aqueous solution of the second soluble carbon source and the first precursor are placed in a culture dish, the first precursor is rolled by stirring, and the aqueous solution of the second soluble carbon source is coated on the surface of the first precursor to freeze to form a coating layer, and then the excess liquid is poured out and the residual liquid in the culture dish is drained to obtain the second precursor. As an embodiment of the present invention, the thickness of the coating layer can be 80~200nm, further can be 100~150nm, and specifically can be 120nm. The present invention forms a coating layer on the surface of the first precursor, and the coating layer serves as a partition layer between the first precursors to prevent the first precursors from being combined with each other; and the coating layer forms a shell on the surface of the first precursor. When performing a subsequent ultrasonic spray-cracking carbonization treatment, the shell is rapidly carbonized to form a coating layer, thereby maintaining the original state of the spray particles (i.e., the first precursor) to provide sufficient time for the subsequent ultrasonic spray-cracking carbonization treatment. During the subsequent ultrasonic spray-cracking carbonization treatment, the ice template (alcohol solvent and water) and the pore-forming agent (such as CTAB) in the second precursor break through the coating layer under high temperature conditions and escape, thereby generating multi-level pores; if the coating layer is not provided, the particles of the multi-level mesoporous carbon finally obtained will be relatively loose.

[0042] After obtaining the second precursor, the present invention mixes the second precursor with a salt solution, and performs ultrasonic spray-cracking carbonization treatment on the obtained second precursor liquid to obtain the multi-level mesoporous carbon. As an embodiment of the present invention, the salt in the salt solution may include one or more of potassium chloride, calcium chloride and sodium chloride, specifically potassium chloride; the concentration of the salt solution may be 20~35wt%, specifically 20wt%, 25wt%, 30wt%, 33wt% or 35wt%; the temperature of the salt solution may be -55~-30°C, further -55~-45°C, specifically -54.9°C. As an embodiment of the present invention, the dosage ratio of the second precursor to the salt solution may be 40~60g:1L, specifically 50g:1L. In the embodiment of the present invention, taking potassium chloride as an example, the potassium chloride aqueous solution is specifically cooled at -54.9°C for 4h and then mixed with the second precursor. In the embodiment of the present invention, a relatively low temperature salt solution is used, so that the second precursor will not melt, thereby maintaining the integrity of the second precursor. Moreover, the salt solution is used as a dispersion medium, which can ensure that the subsequent ultrasonic spray-cracking carbonization treatment proceeds smoothly.

[0043] As an embodiment of the present invention, the conditions of the ultrasonic spray-cracking carbonization treatment may include: the ultrasonic power may be 100~500W, specifically 100W, 200W, 300W, 400W or 500W; the flow rate of the second precursor liquid may be 0.5~3mL / min, specifically 0.5mL / min, 1mL / min, 1.5mL / min, 2mL / min, 2.5mL / min or 3mL / min; the pyrolysis carbonization temperature may be 800~900℃, specifically 800℃, 820℃, 840℃, 860℃, 880℃ or 900℃. In an embodiment of the present invention, the second precursor liquid is specifically injected into an ultrasonic spray device (pre-evacuated and a protective gas is introduced to exhaust the air in the cavity), the tubular furnace is heated to 800-900°C, and a protective gas is introduced into the tubular furnace to exhaust the air in the furnace body; the flow rate of the precursor liquid is adjusted to 0.5-3 mL / min, and the second precursor liquid is sprayed into the furnace body of the tubular furnace through the ultrasonic spray device for ultrasonic spray-cracking carbonization treatment. As an embodiment of the present invention, after the ultrasonic spray-cracking carbonization treatment is completed, the obtained material is specifically naturally cooled under the protective gas protection conditions to obtain the multi-level mesoporous carbon. As an embodiment of the present invention, the protective gas may include one or more of nitrogen, argon and helium, and may specifically be nitrogen. The present invention can quickly form carbon particles through ultrasonic spray-cracking carbonization treatment, which is beneficial to the maintenance of the shape of carbon particles and the reduction of energy consumption.

[0044] As an embodiment of the present invention, after the ultrasonic spray-cracking carbonization treatment is completed, a second solidification treatment may also be included. As an embodiment of the present invention, the temperature of the second solidification treatment may be 700-1400°C, specifically 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C or 1400°C; the insulation time may be 2-6h, specifically 2h, 3h, 4h, 5h or 6h; the second solidification treatment is specifically carried out under protective gas protection conditions. In an embodiment of the present invention, the second solidification treatment is specifically carried out in a tubular furnace. As an embodiment of the present invention, after the second solidification treatment is completed, the obtained material is specifically cooled naturally under protective gas protection conditions to obtain the multi-level mesoporous carbon. In the embodiment of the present invention, the second solidification treatment is beneficial to ensure that the multi-level mesoporous carbon is completely carbonized, increase the uniformity and firmness of the multi-level mesoporous carbon, and at the same time improve the degree of graphitization.

[0045] As an embodiment of the present invention, the second solid treatment further includes impurity removal, and the impurity removal method may include: washing and drying the carbon material obtained after the second solid treatment in sequence. In an embodiment of the present invention, the carbon material after the second solid treatment and natural cooling is specifically washed and dried in sequence; the water used for the washing may specifically be ultrapure water, and the washing method may specifically be immersion washing. As an embodiment of the present invention, the immersion washing temperature may be 10~40°C, further may be 20~30°C, specifically may be 25°C; the time may be 2~10h, further may be 3~5h, specifically may be 4h. As an embodiment of the present invention, the washing further includes filtration, and the obtained solid is dried; the drying temperature may be 60~80°C, specifically may be 70°C; the time may be 4~6h, specifically may be 5~6h.

[0046] The present invention provides a multi-level mesoporous carbon prepared by the preparation method described in the above technical solution, wherein the particle size of the multi-level mesoporous carbon is 100-500nm, further can be 150-400nm, specifically can be 200-300nm; the pore size is ≤35nm, further can be 1-20nm, specifically can be 2-15nm; I D / I G It can be 0.5-1.5, further can be 0.8-1.2, and specifically can be 1.1.

[0047] The main production equipment used in preparing the multi-level mesoporous carbon in the embodiment of the present invention includes a spray device, a low-temperature cold trap, a freeze dryer, an open-hole tubular furnace, an ordinary tubular furnace (without opening) and a glove box, wherein the glove box provides a protective atmosphere, and the spray device, the open-hole tubular furnace and the ordinary tubular furnace are all operated in the glove box; the upper cover of the open-hole tubular furnace is provided with a circular hole with a diameter of 5 to 10 cm and a matching corundum tube (a circular hole is opened in the middle of the corundum tube); wherein the ultrasonic spray-cracking carbonization treatment adopts an open-hole tubular furnace, and the second solid treatment adopts an ordinary tubular furnace. Figure 1 This is a structural diagram of a spray cracking device in an embodiment of the present invention, wherein the spray cracking device comprises a spray device and an open-hole tubular furnace, and the nozzle of the spray device is aligned with a circular hole provided on a cover above the open-hole tubular furnace; the spray device and the open-hole tubular furnace are integrally located in a glove box.

[0048] The related spray method is to atomize and quickly dry the carbon source precursor solution, and then transfer it to a tube furnace for carbonization after grinding. The process involved in this method is often complicated, the formed carbon material is easy to agglomerate, and the microstructure of the carbon material is easy to collapse during the grinding process. At the same time, the carbonization time of this method is long, which often affects the graphitization degree and porosity control of the carbon material, and the energy consumption is high. The present invention adopts a direct spray pyrolysis method, that is, combining the spray method with the tube furnace carbonization method, and directly spraying the second precursor liquid into the tube furnace through a spray device. The atomized droplets can undergo the process of drying, forming and carbonization in a short time. Not only can the particle size of the droplets be controlled to achieve good dispersion and forming degree of uniform particles, but also rapid carbonization under high temperature (800~900℃) conditions helps to maintain the morphological integrity of the particles. Since drying and carbonization are carried out simultaneously, the pore structure on the surface and inside of the carbon material particles can be uniformly formed, thereby ensuring that the interlayer pores are high, which is of great significance for improving the specific surface area and active site exposure rate of the carbon material. In addition, the high temperature environment in the tubular furnace is conducive to improving the degree of graphitization of carbon materials, especially for droplets formed by spraying, which have a large specific surface area, fast heat transfer, and can be quickly carbonized. After settling in the furnace body of the tubular furnace, the high temperature environment continues to carbonize, and the arrangement of the graphite layer is more regular, thereby enhancing the conductivity and thermal stability of the carbon material. The increase in the degree of graphitization not only gives the carbon material excellent conductivity, but also makes it show better cycle stability in electrocatalysis and energy storage devices. The spray-carbonization integrated process in the present invention reduces the risk of particle transmission and structural damage in traditional multi-step operations, improves the degree of particle formation and dispersibility, and enhances the interlayer porosity and degree of graphitization of the carbon material.

[0049] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] 5 g of glucose was mixed with 5 g of ultrapure water, and after stirring to dissolve, 3 g of ethylene glycol and 0.12 g of hexadecyltrimethylammonium bromide (CTAB) were added, and stirring was continued until clarified to obtain a first soluble carbon source solution; the first soluble carbon source solution was injected into an ultrasonic spray device, the nozzle of the ultrasonic spray device was located 10 cm above a cold trap (-80°C), the flow rate of the first soluble carbon source solution was adjusted to 3 mL / min with an ultrasonic spray-freezing treatment at an ultrasonic power of 200 W, and ice beads were collected in a glass container in the cold trap, and the ice beads were sieved with a 200-mesh sieve to obtain well-dispersed ice beads, and then placed in a freeze dryer (-80°C) for a first solid treatment for 4 hours to obtain a first precursor (particle size of 100-500 nm);

[0052] Put 10 mL of saturated glucose aqueous solution (0° C.) and the first precursor into a culture dish, stir with a medicine spoon to make the first precursor roll, and coat the saturated glucose aqueous solution on the surface of the first precursor to freeze to form a coating layer, then pour out the excess liquid and drain the residual liquid in the culture dish to obtain a second precursor;

[0053] A 35wt% potassium chloride aqueous solution was cooled at -54.9°C for 4h, and then 50mL of the potassium chloride aqueous solution was stirred and mixed with 2.5g of the second precursor, and the obtained second precursor liquid was injected into an ultrasonic spray device (pre-evacuated and nitrogen was introduced to exhaust the air in the cavity); the tubular furnace was heated to 900°C, and nitrogen was introduced into the tubular furnace for 2h to exhaust the air in the furnace body; the flow rate of the second precursor liquid was adjusted to 3mL / min, and the second precursor liquid was sprayed into the furnace body of the tubular furnace through the ultrasonic spray device under the condition of an ultrasonic power of 200W to perform ultrasonic spray-cracking carbonization treatment, and then naturally cooled under nitrogen protection conditions to obtain carbon black particles;

[0054] The carbon black particles were subjected to a second solidification treatment at 900°C for 3 hours under nitrogen protection in a tubular furnace, and then naturally cooled under nitrogen protection. The obtained solid particles were soaked in ultrapure water at 25°C for 4 hours, and then filtered. The solid was dried at 70°C for 6 hours to obtain multi-level mesoporous carbon.

[0055] Example 2

[0056] The operation is carried out in accordance with the method of Example 1, except that the mass of glucose used in preparing the first precursor is 8 g and the mass of water is 8 g; the flow rate of the first soluble carbon source solution during the ultrasonic spray-freezing treatment is 2 mL / min; the flow rate of the second precursor solution during the ultrasonic spray-cracking carbonization treatment is 2 mL / min and the temperature of the tubular furnace is 800°C; the temperature of the tubular furnace during the second solid treatment is 800°C.

[0057] Comparative Example 1

[0058] The operation is carried out in accordance with the method of Example 1, except that after obtaining the second precursor, the second precursor is placed in a freeze dryer (-80°C) for freeze drying for 12 hours, then ground into powder (particle size is 200-500nm), and carbonized at 900°C for 3 hours in a tubular furnace under nitrogen protection conditions, and then naturally cooled under nitrogen protection conditions, the obtained carbon material is soaked in ultrapure water at 25°C for 4 hours, and then filtered, and the solid is dried at 70°C for 6 hours to obtain multi-level mesoporous carbon.

[0059] Comparative Example 2

[0060] The method of Example 1 is referred to, except that the saturated glucose aqueous solution is omitted, that is, the saturated glucose aqueous solution is not used to form a coating layer on the surface of the first precursor, and the first precursor is directly mixed with the potassium chloride aqueous solution for subsequent ultrasonic spray-cracking carbonization treatment.

[0061] The amounts of raw materials and operating conditions in Examples 1-2 and Comparative Examples 1-2 are shown in Table 1, and the conditions not mentioned are the same as those in Example 1.

[0062] Table 1 Raw material dosage and operating conditions in Examples 1-2 and Comparative Examples 1-2

[0063]

[0064] Test Example 1

[0065] Figure 2 This is the SEM image of the multi-level mesoporous carbon prepared in Example 1. Figure 3 This is a SEM image of the multi-level mesoporous carbon prepared in Example 2. The results show that the multi-level mesoporous carbon particles have good molding degree and good particle independence, mainly because a higher spray flow rate is used during the ultrasonic spray-freezing process, and the atomized precursor particles are spherical during the spraying process and then quickly cooled in the cold trap; the liquid in the raw material formula of Example 2 has a larger specific gravity and lower viscosity, and the atomized particles are more easily deformed into an elliptical or rod-shaped shape during the spraying process.

[0066] Figure 4The SEM image of the multi-level mesoporous carbon prepared in Comparative Example 1 shows that the multi-level mesoporous carbon prepared in Comparative Example 1 has poor molding degree, and the particles stick together and agglomerate. This is because Comparative Example 1 does not directly perform ultrasonic spray-cracking carbonization treatment but adopts freeze-drying-grinding-carbonization process, and cannot form atomized particles of smaller size.

[0067] Figure 5 This is a SEM image of the multi-level mesoporous carbon prepared in Comparative Example 2. The results show that the multi-level mesoporous carbon prepared in Comparative Example 2 is severely deformed into an elliptical shape, and the pores are loose and rough.

[0068] Figure 6 This is a comparison diagram of the pore distribution of the multi-level mesoporous carbon prepared in Example 1 and Comparative Example 2. The results show that the multi-level mesoporous carbon in Example 1 has a wider pore size distribution range (≤35nm), with obvious peaks at 6nm and 10nm, while the pore size of the multi-level mesoporous carbon in Comparative Example 2 is concentrated at 25nm, with a slightly smaller peak at 10nm, and a smaller pore size distribution range. This indicates that the presence of the coating layer plays a solidifying role, allowing the atomized precursor particles (i.e., the second precursor) to maintain a good original morphology before carbonization, while generating multi-level pores.

[0069] Figure 7 This is a particle size distribution diagram of the multi-level mesoporous carbon prepared in Example 1. The results show that the particle size of the multi-level mesoporous carbon in Example 1 is mainly concentrated at around 200 nm.

[0070] Figure 8 This is a particle size distribution diagram of the multi-level mesoporous carbon prepared in Example 2. The results show that the particle sizes of the multi-level mesoporous carbon in Example 2 are mainly concentrated between 120 and 140 nm.

[0071] Fig. 9 is a Raman spectrum of carbon black particles obtained after ultrasonic spray-cracking carbonization treatment in Example 1, Fig.10 The Raman spectra of the multi-level mesoporous carbon prepared in Example 1 and Comparative Example 1 are compared. D / I G The lower the value, the higher the degree of graphitization. The results show that in Example 1, the second solid treatment after the ultrasonic spray-cracking carbonization treatment is beneficial to improving the degree of graphitization of the multi-level mesoporous carbon; and compared with Comparative Example 1, the multi-level mesoporous carbon prepared by direct spray pyrolysis method in Example 1 has a higher degree of graphitization.

[0072] From the above results, it can be seen that the present invention adopts ice template method and pore-forming agent to prepare precursor and adopts direct spray pyrolysis method to prepare multi-level mesoporous carbon, and the carbonization speed is fast. At the same time, the multi-level mesoporous carbon has good particle forming degree and uniform particles, good particle dispersibility, high degree of graphitization, large interlayer pores (specifically refers to large gaps between particles), and has micropores and mesoporous multi-level pores. The following is a detailed description: In the present invention, the first soluble carbon source, pore-forming agent, alcohol solvent and water are mixed to form water mist particles by ultrasonic spraying, and ice beads are quickly frozen in a cold trap, and no fixed agglomeration is generated between the ice beads; when the coating layer is subsequently formed, the boundary between the ice beads is further increased due to the temperature difference. In the process of ultrasonic spray-pyrolysis carbonization treatment of the present invention, the water mist particles formed by the second precursor liquid have a large contact area with the outside world, can be quickly carbonized, and the particles are not easily agglomerated during the carbonization process because of the lack of connectivity between the water mist particles, and finally form multi-level mesoporous carbon with good particle forming degree, uniform particles and good dispersibility. In the present invention, ultrasonic spray-cracking carbonization treatment and the second solidification treatment are beneficial to improving the graphitization degree of multi-level mesoporous carbon. In the present invention, alcohol solvents and water act as ice templates during ultrasonic spray-freezing treatment, and evaporate during ultrasonic spray-cracking carbonization treatment, which is beneficial to improving the interlayer pores of multi-level mesoporous carbon; the present invention adopts an intermittent ultrasonic spray method, and the first layer of carbon black particles is formed after the first water mist particles are carbonized. After the second water mist particles fall, they first contact the first layer of formed carbon black particles with a semi-solidified precursor, and then form a second layer of formed carbon black particles. A large gap will be generated between the two layers of carbon black particles formed at different times. In the present invention, a microporous structure and a mesoporous structure are constructed by a pore-forming agent (such as CTAB, which will vaporize and escape at 550°C) and an ice template (alcohol solvent and water), wherein the aqueous solution of the second soluble carbon source will quickly cool down and freeze after contacting the first precursor at a lower temperature, forming a coating layer on the surface of the first precursor, and a carbon shell will be formed by carbonization during the ultrasonic spray-cracking carbonization treatment. In the present invention, the entire ultrasonic spray-cracking carbonization treatment process is carried out under the condition of the presence of protective gas, which can quickly eliminate the template and realize carbonization molding.

[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing multi-level mesoporous carbon, characterized in that: The following steps are involved: A first soluble carbon source, a pore-forming agent, an alcohol solvent and water are mixed, and the obtained first soluble carbon source solution is subjected to ultrasonic spray-freezing treatment, and then subjected to a first solidification treatment to obtain a first precursor; Coating an aqueous solution of a second soluble carbon source on the surface of the first precursor, and freezing the aqueous solution on the surface of the first precursor to form a coating layer, thereby obtaining a second precursor; The second precursor is mixed with a salt solution, and the obtained second precursor liquid is subjected to an ultrasonic spray-cracking carbonization treatment to obtain the multi-level mesoporous carbon.

2. The preparation method according to claim 1, characterized in that: The first soluble carbon source and the second soluble carbon source independently include one or more of glucose, sucrose and fructose; the pore-forming agent includes a non-ionic pore-forming agent, and the alcohol solvent includes one or more of ethylene glycol, ethanol, propanol and isopropanol; the mass ratio of the first soluble carbon source, the pore-forming agent, the alcohol solvent and water in the first soluble carbon source solution is 1~10:0.02~0.2:1~5:5~8.

3. The preparation method according to claim 1 or 2, characterized in that: The conditions of the ultrasonic spray-freezing treatment include: the ultrasonic power is 100-500W, the flow rate of the first soluble carbon source solution is 1-5mL / min, and the freezing temperature is <-60°C.

4. The preparation method according to claim 3, characterized in that: The temperature of the first solidification treatment is -120~-20°C, and the time is 2~6h.

5. The preparation method according to claim 1 or 2, characterized in that: The aqueous solution of the second soluble carbon source has a concentration of 50-80 wt % and a temperature of -5-5°C.

6. The preparation method according to claim 5, characterized in that: The particle size of the first precursor is 100-500 nm, and the thickness of the coating layer is 80-200 nm.

7. The preparation method according to claim 1, characterized in that: The salt in the salt solution includes one or more of potassium chloride, calcium chloride and sodium chloride; the concentration of the salt solution is 20-35wt%, and the temperature of the salt solution is -55--30°C.

8. The preparation method according to claim 1 or 7, characterized in that: The conditions of the ultrasonic spray-cracking carbonization treatment include: the ultrasonic power is 100-500W, the flow rate of the second precursor liquid is 0.5-3mL / min, and the cracking carbonization temperature is 800-900°C.

9. The preparation method according to claim 1, characterized in that: The ultrasonic spray-cracking carbonization treatment also includes a second solidification treatment; the temperature of the second solidification treatment is 700-1400° C., and the insulation time is 2-6 hours.

10. The multi-level mesoporous carbon prepared by the preparation method according to any one of claims 1 to 9, wherein the particle size is 100 to 500 nm, the pore size is ≤ 35 nm, and the D / I G It is 0.5~1.5.

Citation Information

Patent Citations

  • Nitrogen-containing large-pore-volume porous carbon material, and preparation method and application thereof

    CN108123110A

  • Hierarchical porous carbon material used for flexible supercapacitor and production method thereof

    CN109850866A